Medical Swimming Cellbots. Issue 10 (15th September 2022) - Zhang, Hongyue; Li, Zesheng; He, Qiang
Abstract : To address the issue that synthetic swimming nanorobots are susceptible to immune clearance and fouling in vivo, swimming hybrid cell‐based robots (cellbots) composed of living cells have been developed. Swimming cellbots use living cells such as sperm, bacteria, and algae as fabrication units to obtain the swimming capacity, which can be functionalized by adding different kinds of functional components and cargoes. Swimming cellbots not only inherit the biological functions of natural cells, but also can realize diverse locomotion modes under the action of their synthetic parts. This perspective highlights the fabrication, functionalization and multimode motion control of swimming cellbots, and possible medical application. As a representative example of swimming cellbots, dual‐responsive neutrobots have two driving modes: rotating magnetic field actuation and chemotactic locomotion, which can be utilized to cross the blood–brain barrier and target the glioblastoma in mice. The delivery efficiency of these drug‐loaded neutrobots can reach about 10% which is significantly higher than that of traditional nanocarriers. Such swimming cellbots may load different types of drugs and can be navigated through the combination of natural chemotaxis and externally physical fields such as magnetic, optical, and ultrasonic fields which may have potential in biomedical fields. Abstract : Swimming cellbots with multifunction of motility and in vivo medical treatment means are presented, which are built by cells like sperm, bacteria, erythrocyte, and leukocyte, as well as synthetic materials like nanoparticles, drugs, and vesicles. The dual‐responsive neutrobots are highlighted as an advanced example of multimode locomotion ability and in vivo target delivery.